Interface optimization type material, preparation method and application thereof, preparation method of positive electrode material, positive electrode plate and zinc ion battery
By coating manganese oxides with polyaniline and forming Mn-N bonds, the poor capacity and structural stability of manganese dioxide positive electrode materials are solved, and a water-based zinc-manganese battery with high cycling stability and high specific capacity is achieved.
Patent Information
- Application Number
- CN202411885494.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
The manganese dioxide positive electrode material has problems such as poor capacity, poor capacity attenuation and rate capability, and the Mn3+ disproportionation reaction leads to collapse of the positive electrode/electrolyte interface structure or irreversible MnO2 deposition.
The manganese oxide is coated in situ by polyaniline to form a polyaniline layer and form a Mn-N bond, inhibiting the dissolution of manganese and structural collapse, promoting proton deintercalation, and preventing the formation of irreversible zinc manganate products.
The cycle stability and specific capacity of the manganese oxide positive electrode are significantly improved, and a high-energy and long-life water-based zinc-manganese battery is constructed, which can maintain good battery performance under high current density.
Smart Images

Figure CN119674016A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical energy storage technology, and in particular to an interface optimized material and a preparation method and use thereof, a preparation method of a positive electrode material, a positive electrode sheet and a zinc ion battery. Background Art
[0002] In the current situation of increasing shortage of traditional fossil fuel resources, achieving carbon peak regulation and carbon neutrality goals has become an urgent task, so it is particularly urgent to develop new energy storage technologies with high safety and environmental protection. In this context, aqueous zinc batteries have low cost and high theoretical specific capacity (820mAh g -1 ) and low redox potential (-0.76V compared to the standard hydrogen electrode), showing great development potential.
[0003] The energy and life of the battery are closely related to the physicochemical properties of the cathode material. Compared with the reported vanadium-based oxides, Prussian blue analogs (PBAs) and some organic compounds, manganese dioxide cathode has a high theoretical capacity (based on the two-electron transfer Mn 4+ / Mn 2+ 616mAh g -1 ) and suitable operating voltage. However, manganese dioxide positive electrodes also face many challenges. Due to Jahn-Teller distortion, low conductivity and slow ion diffusion kinetics, they often have problems such as poor capacity, capacity decay and poor rate capability. More seriously, Mn3 + The disproportionation reaction further exacerbates the structural collapse of the cathode / electrolyte interface (CEI) or the irreversible MnO2 deposition phenomenon.
[0004] The existing public patent (CN202211669600) improves the battery rate performance and cycle stability by forming a polyaniline coating on the surface of manganese dioxide. However, the present application found in the study that it is difficult to evenly coat manganese dioxide with polyaniline in deionized water, and the charge and discharge cycle process easily causes the polyaniline to fall off, ultimately leading to poor cycle stability. What's more serious is that most of the existing zinc-manganese battery research is based on the MnO2 / Mn3+ single electron transfer mechanism, which is difficult to meet the current battery requirements for higher energy density energy storage systems.
[0005] In order to solve the above problems, this application is proposed. Summary of the invention
[0006] The present application found in the research that it is very important to find an efficient and low-cost organic uniformly coated modified manganese dioxide or other manganese oxide modification strategy. In particular, the uniformly coated polymer layer can effectively promote the deintercalation of hydrogen ions rather than zinc ions, inhibit the formation of irreversible zinc manganate products and promote the MnO2 / Mn2+ mechanism, thereby building a high-performance aqueous zinc-manganese battery with high capacity and long cycle life.
[0007] The first aspect of the present application provides an interface-optimized material, the interface-optimized material comprising: polyaniline and manganese oxide;
[0008] The polyaniline is coated on the surface of the manganese oxide to form a polyaniline layer, and a Mn-N bond is formed between the polyaniline and the manganese oxide.
[0009] Preferably, the mass ratio of the polyaniline to the manganese oxide is (0.05-0.30):1.
[0010] Preferably, the thickness of the polyaniline layer is 5-10 nm.
[0011] The manganese oxide is one or more of manganese dioxide, dimanganese trioxide or trimanganese tetraoxide.
[0012] Preferably, the manganese dioxide is tunnel-type manganese dioxide, and the nanowire length is 50 to 500 nanometers.
[0013] A second aspect of the present application provides a method for preparing an interface optimized material, the method comprising the following steps:
[0014] dispersing manganese oxide and polyaniline in an organic solvent and stirring to obtain a mixed solution;
[0015] After adding the conductive powder to the above mixed solution, transfer it to a sealed hydrothermal kettle and heat it at 60°C to 80°C for 4 to 6 hours;
[0016] After the reaction is completed, part of the conductive powder is removed by centrifugation, and then dried to obtain the interface optimized material.
[0017] Preferably, the mass ratio of the polyaniline to the manganese oxide is (0.05-0.30):1;
[0018] The mass ratio of the conductive powder to the manganese oxide is (0.02-0.10):1.
[0019] Preferably, the organic solvent is selected from one or more of ethanol, ethylene glycol, acetone and N-methylpyrrolidone.
[0020] Preferably, the stirring time is 6 to 24 hours.
[0021] Preferably, the conductive powder is graphene or graphene oxide.
[0022] The third aspect of the present application provides the use of the interface optimized material described in the first aspect as a positive electrode material for a zinc ion battery.
[0023] The fourth aspect of the present application provides a method for preparing a positive electrode material, which comprises the following steps: adding the interface optimized material of the first aspect: conductive agent: binder in a mass ratio of (6 to 8): (3 to 1): 1 to a solvent, grinding and mixing, coating or rolling it onto a current collector, and drying to obtain a positive electrode material.
[0024] Preferably, the conductive agent includes one or more of graphene, acetylene black, activated carbon, carbon nanotubes, and Super P.
[0025] Preferably, the solvent is N-methylpyrrolidone or water.
[0026] Preferably, the loading amount of the interface optimized material on the current collector is 2.0 to 30.0 mg cm -2 .
[0027] Preferably, the current collector is selected from: carbon cloth, titanium foil or stainless steel mesh.
[0028] The drying condition was 80° C. for 24 hours.
[0029] Preferably, the binder is selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC).
[0030] The finally obtained positive electrode material of the present application contains the interface optimized material of the first aspect and a conductive agent.
[0031] A fifth aspect of the present application provides a positive electrode sheet, the positive electrode sheet comprising: a positive electrode material layer; the positive electrode material layer comprises the interface optimized material described in any one of the first aspects or the positive electrode material prepared by the preparation method described in any one of claims 5 to 10.
[0032] A sixth aspect of the present application provides a zinc ion battery, the battery comprising the positive electrode sheet described in the fifth aspect.
[0033] Preferably, the electrolyte of the battery comprises manganese sulfate and zinc sulfate.
[0034] Preferably, the molar concentration of manganese sulfate is 0.05-0.6 M, and the molar concentration of zinc sulfate is 0.05-3 M. The negative electrode sheet of the battery is a metal zinc foil. The thickness of the metal zinc foil is 30-100 microns, and it is sealed and assembled into a CR2032 battery under a pressure of 50-70 MPa for electrochemical performance testing.
[0035] Compared with the prior art, the technical solution of this application has the following advantages:
[0036] 1. The present application provides an organic-inorganic interface optimized positive electrode material that promotes proton deintercalation. The present application in situ coats manganese oxide with polyaniline to form an organic / inorganic reaction interface on the surface of manganese oxide, and the material exhibits excellent electrochemical properties. Specifically, the Mn-N bond formed between polyaniline and manganese oxide can effectively inhibit the dissolution of manganese, prevent the structural collapse of manganese oxide during the cycle, and thus significantly improve the cycle stability of the manganese oxide positive electrode. Bipolar polyaniline has oxidation and reduction units, which can act as a "pH buffer" and "local proton reservoir", greatly promoting the embedding of protons rather than zinc ions, thereby inhibiting the generation of ZnMn2O4 and the irreversible deposition of "dead manganese", and thus can construct a reversible MnO2 / Mn 3+ and MnO2 / Mn 2+ High-energy and long-life aqueous zinc-manganese batteries with dual energy storage mechanisms.
[0037] 2. The polyaniline coating in the prior art occurs in water, and polyaniline cannot be dissolved in water, so it will not form Mn-N bonds with manganese oxide due to interface interaction.
[0038] The characteristics of the preparation method of the present application are as follows: The hydrothermal reaction of the present application is carried out in an organic solvent. The organic solvent can prevent the agglomeration between manganese oxide particles, maintain a good dispersion state, and form a stable suspension. There is a strong interaction between polyaniline molecules, which is easy to agglomerate. The organic solvent can dissolve part of the polyaniline, effectively reduce the attraction between polyaniline particles, and allow the polyaniline to be more evenly coated on the surface of manganese oxide. At the same time, the addition of organic solvent improves the interfacial compatibility between polyaniline and manganese oxide, allowing the two to form a more stable interaction at the interface, generate Mn-N bonds, and reduce interface defects and charge transfer resistance.
[0039] The functions of graphene or graphene oxide are: 1. It is used to disperse polyaniline so that it can be coated more evenly on the surface of manganese oxide. 2. Graphene has excellent conductivity and can build an efficient conductive network with interface-optimized materials to enhance the overall conductivity.
[0040] 3. The material of the present application can improve the specific capacity and cycle stability of the manganese oxide positive electrode of aqueous zinc ion batteries. Specifically, it is: Figure 8 It can be seen that at a current density of 0.5A g -1 Under the conditions of , after 150 charge-discharge cycles, the capacity retention rate of the positive electrode material of Example 4 (P-MnO2 in the figure) is almost perfectly maintained at 100%; its specific capacity is still as high as 341 mAh g -1, showing extremely excellent cycle stability. Fig. 9 , 10 It can be seen that the positive electrode material of Example 4 has a high conductivity at 0.2, 0.5, 1.0, 1.5, 2.0, 3.0 and 5.0A g -1 The average discharge capacities at 4000 mAh g were 510.2, 406.3, 329.8, 283.3, 250.6, 209.7 and 164.1 mAh g -1 The overall performance shows a high capacity output and a relatively stable change with current density. Compared with the positive electrode of the unmodified similar material in Example 1 (MnO2 in the figure), its rate performance has a significant advantage. -1 The first 20 cycles from the initial 380mAh g -1 Increased to 520mAh g -1 , a significant capacity increase can be observed, which indicates that with the formation of “proton self-confinement domains” within the PANI layer, the MnO2 / Mn 2+ The reaction is gradually stimulated. Considering the interfacial Mn-N bonds and the reversible MnO2 deposition reaction, the excellent battery performance of P-MnO2 can be attributed to the MnO2 being encapsulated in the proton-rich polyaniline protective layer. Fig.13 It can be seen that at 5000mA g -1 Under high current density, the positive electrode material of Example 4 still exhibits amazing long cycle stability. After up to 10,000 charge and discharge cycle tests, its capacity retention rate is still as high as 94%, the battery can still maintain excellent stability, and its specific capacity can also be maintained at a good level, which fully demonstrates the excellent performance of the positive electrode material under high current conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a scanning electron microscope image of manganese dioxide provided in Example 1 of the present application;
[0042] Figure 2 This is a scanning electron microscope image of manganese dioxide provided in Example 1 of the present application;
[0043] Figure 3 A high-resolution transmission electron microscopy image of the interface-optimized material provided in Example 1 of the present application;
[0044] Figure 4 This is the XPS spectrum of N1s of the interface optimized material provided in Example 1 of the present application;
[0045] Figure 5 Raman spectra of the positive electrode material, commercial polyaniline and manganese dioxide provided in Example 1 of the present application;
[0046] Figure 6Element distribution diagram of the positive electrode material provided in Example 1 of the present application;
[0047] Figure 7 XRD images of manganese dioxide and positive electrode materials provided in Example 1 of the present application;
[0048] Figure 8 The positive electrode material provided in Example 4 of the present application is used as the positive electrode of a zinc ion battery at a current density of 500 milliamperes per gram (abbreviated as @0.5Ag -1 ) under long charge and discharge cycle diagram (the arrow on the left corresponds to the specific capacity under different number of cycles, and the arrow on the right corresponds to the coulomb efficiency under different number of cycles);
[0049] Fig. 9 The electrochemical rate performance diagram of the positive electrode materials provided in Example 4 and Comparative Example 1 of the present application as the positive electrode of the zinc ion battery, the current density is 0.2, 0.5, 1, 1.5, 2, 3, 5A g -1 ;
[0050] Fig.10 The positive electrode material provided in Example 1 of the present application is used as the charge and discharge curve of the positive electrode of the zinc ion battery. The current densities used for constant current charge and discharge are 0.2, 0.5, 1, 1.5, 2, 3, and 5A g -1 ;
[0051] Fig.11 The positive electrode materials provided in Examples 1, 2, 3, 4, and 5 of the present application are respectively used as positive electrodes of zinc ion batteries at a current density of 200 milliamperes per gram (abbreviated as @0.2A g -1 )'s charge and discharge long cycle comparison chart;
[0052] Fig.12 The positive electrode materials provided in Examples 6 and 7 of the present application and Comparative Example 1 are respectively used as positive electrodes of zinc ion batteries at a current density of 1000 milliamperes per gram (abbreviated as @1.0A g -1 )'s charge and discharge long cycle comparison chart;
[0053] Fig.13 The positive electrode materials provided in Example 4 and Comparative Example 1 of the present application are respectively used as positive electrodes of zinc ion batteries at a current density of 5000 milliamperes per gram (abbreviated as @5.0A g -1 ) is a charge-discharge long cycle comparison diagram (the two curves near the left arrow are the specific capacities of P-MnO2 and MnO2 positive electrodes at different numbers of cycles, and the arrow on the right is the Coulomb efficiency of P-MnO2 and MnO2 positive electrodes at different numbers of cycles). DETAILED DESCRIPTION
[0054] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0055] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods. The experimental methods in the following examples without specifying specific conditions are usually measured according to national standards. If there is no corresponding national standard, it is carried out according to the general international standards, conventional conditions, or the conditions recommended by the manufacturer.
[0056] The manganese dioxide used in the examples and comparative examples was purchased and characterized to show that it is tunnel-type manganese dioxide, and the nanowires of the manganese dioxide are 50 to 500 nanometers long.
[0057] Example 1
[0058] A method for preparing a positive electrode material, the method comprising:
[0059] S1. Disperse polyaniline and manganese dioxide in ethylene glycol at a mass ratio of 0.05:1 and stir evenly for 24 hours;
[0060] S2. Graphene oxide was added to the mixture, the mass ratio of graphene oxide to manganese dioxide was 0.02:1, and then transferred to a sealed polytetrafluoroethylene-lined high-pressure hydrothermal autoclave, and placed in an oven for reaction at 80 ° C for 6 hours;
[0061] S3. After the reaction is completed, centrifuge and dry to obtain a polyaniline-coated manganese dioxide active material (named polyaniline@manganese dioxide), which is the interface optimized material of the present application (denoted as P-MnO2).
[0062] S4. Mix polyaniline@manganese dioxide: conductive agent (graphene): binder (polyvinylidene fluoride, PVDF) in a mass ratio of 7:2:1, add N-methylpyrrolidone (NMP) and grind and mix well, then coat it on a carbon cloth current collector and dry it at 80°C for 24 hours to obtain a polyaniline@manganese dioxide modified positive electrode material.
[0063] Example 2
[0064] S1. Disperse polyaniline and manganese dioxide in ethylene glycol at a mass ratio of 0.067:1 and stir evenly for 24 hours;
[0065] S2. Graphene oxide was added to the mixture, the mass ratio of graphene oxide to manganese dioxide was 0.02:1, and then transferred to a sealed 100 ml polytetrafluoroethylene-lined high pressure hydrothermal autoclave, and placed in an oven for reaction at 60 ° C for 4 hours;
[0066] S3. After the reaction is completed, centrifuge and dry to obtain a polyaniline-coated manganese dioxide active material (named polyaniline @ manganese dioxide), which is the interface optimized material of the present application;
[0067] S4. Mix polyaniline@manganese dioxide: conductive agent (acetylene black): binder (polytetrafluoroethylene, PTFE) in a mass ratio of 6:3:1, add NMP and grind and mix well, then coat it on a stainless steel current collector and dry it at 80°C for 24 hours to obtain a polyaniline@manganese dioxide modified positive electrode material.
[0068] Example 3
[0069] S1. Disperse polyaniline and manganese dioxide in ethanol at a mass ratio of 0.1:1 and stir evenly for 24 hours;
[0070] S2. Graphene oxide was added to the mixture, the mass ratio of graphene oxide to manganese dioxide was 0.02:1, and then transferred to a sealed 100 ml polytetrafluoroethylene-lined high pressure hydrothermal autoclave, and placed in an oven for reaction at 80 ° C for 5 hours;
[0071] S3. After the reaction is completed, centrifuge and dry to obtain a polyaniline-coated manganese dioxide active material (named polyaniline @ manganese dioxide), which is the interface optimized material of the present application;
[0072] S4. Mix polyaniline@manganese dioxide: conductive agent (carbon nanotubes): binder (carboxymethyl cellulose, CMC) in a mass ratio of 8:1:1, add water and grind to mix, then coat on a carbon cloth current collector and dry at 80°C for 24 hours to obtain a polyaniline@manganese dioxide modified positive electrode material.
[0073] Example 4
[0074] S1. Disperse polyaniline and manganese dioxide in ethylene glycol at a mass ratio of 0.2:1 and stir evenly for 24 hours;
[0075] S2. Graphene oxide was added to the mixture, the mass ratio of graphene oxide to manganese dioxide was 0.02:1, and then transferred to a sealed polytetrafluoroethylene-lined high-pressure hydrothermal autoclave, and placed in an oven for reaction at 80 ° C for 5 hours;
[0076] S3. After the reaction is completed, centrifuge and dry to obtain a polyaniline-coated manganese dioxide active material (named polyaniline@manganese dioxide), which is the interface optimized material of the present application.
[0077] S4. Mix polyaniline@manganese dioxide: conductive agent (activated carbon): binder (polyvinylidene fluoride, PVDF) in a mass ratio of 7:2:1, add N-methylpyrrolidone (NMP) and grind and mix well, then coat it on a titanium foil current collector and dry it at 80°C for 24 hours to obtain a polyaniline@manganese dioxide modified positive electrode material.
[0078] Example 5
[0079] A method for preparing a positive electrode material, the method comprising:
[0080] S1. Disperse polyaniline and manganese dioxide in ethylene glycol at a mass ratio of 0.3:1 and stir evenly for 24 hours;
[0081] S2. Graphene oxide was added to the mixture, the mass ratio of graphene oxide to manganese dioxide was 0.02:1, and then transferred to a sealed polytetrafluoroethylene-lined high-pressure hydrothermal autoclave, and placed in an oven for reaction at 80 ° C for 5 hours;
[0082] S3. After the reaction is completed, centrifuge and dry to obtain a polyaniline-coated manganese dioxide active material (named polyaniline@manganese dioxide), which is the interface optimized material of the present application.
[0083] S4. Mix polyaniline@manganese dioxide: conductive agent (carbon nanotubes): binder (polyvinylidene fluoride, PVDF) in a mass ratio of 7:2:1, add NMP and grind and mix well, then coat it on a carbon cloth current collector and dry it at 80°C for 24 hours to obtain a polyaniline@manganese dioxide modified positive electrode material.
[0084] Example 6
[0085] A method for preparing a positive electrode material, the method comprising:
[0086] S1. Disperse polyaniline and manganese tetraoxide in ethylene glycol at a mass ratio of 0.2:1 and stir evenly for 24 hours;
[0087] S2. Graphene oxide was added to the mixture, the mass ratio of graphene oxide to manganese tetraoxide was 0.02:1, and then transferred to a sealed polytetrafluoroethylene-lined high-pressure hydrothermal autoclave, and placed in an oven for reaction at 80 ° C for 5 hours;
[0088] S3. After the reaction is completed, centrifuge and dry to obtain a polyaniline-coated manganese tetraoxide active material (named polyaniline@manganese tetraoxide), which is the interface optimized material of the present application.
[0089] S4. Mix polyaniline@manganese tetraoxide: conductive agent (Super P): binder (polyvinylidene fluoride, PVDF) in a mass ratio of 7:2:1, add NMP and grind and mix well, then coat it on a carbon cloth current collector and dry it at 80°C for 24 hours to obtain a polyaniline@manganese tetraoxide modified positive electrode material.
[0090] Example 7
[0091] A method for preparing a positive electrode material, the method comprising:
[0092] S1. Disperse polyaniline and manganese trioxide in acetone at a mass ratio of 0.2:1 and stir evenly for 24 hours;
[0093] S2. Graphene oxide was added to the mixture, the mass ratio of graphene oxide to manganese trioxide was 0.02:1, and then transferred to a sealed polytetrafluoroethylene-lined high-pressure hydrothermal autoclave, and placed in an oven for reaction at 80 ° C for 5 hours;
[0094] S3. After the reaction is completed, centrifuge and dry to obtain a polyaniline-coated manganese trioxide active material (named polyaniline@manganese trioxide), which is the interface optimized material of the present application.
[0095] S4. Mix polyaniline@manganese trioxide: conductive agent (graphene): binder (polyvinylidene fluoride, PVDF) in a mass ratio of 7:2:1, add NMP and grind and mix well, then coat it on a carbon cloth current collector and dry it at 80°C for 24 hours to obtain a polyaniline@manganese trioxide modified positive electrode material.
[0096] Comparative Example 1
[0097] Manganese dioxide: conductive agent: binder (polyvinylidene fluoride, PVDF) was added to NMP at a mass ratio of 7:2:1, ground and mixed, coated on carbon cloth, and dried at 80° C. for 24 hours to obtain a manganese dioxide positive electrode material.
[0098] Material characterization and performance testing:
[0099] The positive electrode materials provided in Examples 1 to 5 and Comparative Example 1 were tested by scanning electron microscopy. Since the results are similar, only the test results of Example 1 are used as an example for illustration below.
[0100] Figure 1 a and b are scanning electron microscope images of the manganese dioxide provided in Example 1. The manganese dioxide exhibits a unique nanoflower structure, which is formed by a large number of nanowires that are aggregated and stacked.
[0101] Figure 2This is an enlarged view of the scanning electron microscope image of the manganese dioxide provided in Example 1. It can be seen that the manganese dioxide used is tunnel-type manganese dioxide, and the length of the nanowires of the manganese dioxide is 50nm-500nm.
[0102] Figure 3 A high-resolution transmission electron microscopy image of the interface-optimized material is provided for Example 1. Figure 3 It can be seen that polyaniline without lattice structure is uniformly coated on the surface of manganese dioxide, and the thickness of the polyaniline layer is about 7.8 nm.
[0103] Figure 4 This is the XPS spectrum of N1s of the interface optimized material provided in Example 1 of the present application. From the in-depth analysis of the figure, it can be seen that in the XPS N 1s spectrum, characteristic peak signals of NH bonds and C=N bonds corresponding to the inherent characteristics of polyaniline itself are presented. These peak positions indicate the typical characteristics of the molecular structure of polyaniline. It is worth noting that a new peak morphology is observed at 399.5eV. After rigorous judgment, it is determined that this is the peak position corresponding to the newly generated Mn-N bond. This discovery fully confirms that the Mn-N bond is successfully formed between manganese dioxide and polyaniline due to the interface interaction.
[0104] Figure 5 Raman spectra of the positive electrode material, commercial polyaniline (PANI), and manganese dioxide provided in Example 1 of the present application. As can be seen from the figure, the Raman spectrum of P-MnO2 shows that the Mn-O bond belongs to the characteristic peak of manganese dioxide, and the CN bond belongs to the characteristic peak of polyaniline. It is worth noting that the new peak of P-MnO2 appears at a higher wavenumber position than the Mn-O bond of the original MnO2, which means that a chemical bond (Mn-N) is formed between manganese dioxide and polyaniline.
[0105] Figure 6 Element distribution diagram of the positive electrode material provided in Example 1. As can be seen from the figure, the polyaniline @ manganese dioxide active material presents a regular spherical appearance after being fully mixed with the conductive agent. These materials are intertwined with each other, successfully building an efficient three-dimensional conductive network architecture, and building a "high-speed channel" for the rapid transmission of electrons. Further exploration with the help of elemental EDS analysis technology shows that the key elements C, N, Mn, and O are evenly and densely distributed on the surface of the material, which strongly proves the uniformity of the composite material.
[0106] Figure 7 XRD spectra of the positive electrode materials provided for Example 1 and Comparative Example 1. From the XRD spectra presented in the figure, it can be clearly found that compared with the original manganese dioxide spectrum, the spectrum of the polyaniline@manganese dioxide modified positive electrode material obviously has more characteristic peaks unique to polyaniline and conductive materials. This indirectly confirms the successful compounding of polyaniline with manganese dioxide and conductive agent.
[0107] The positive electrode materials provided in Examples 1 to 7 and Comparative Example 1 were used with the same concentration of manganese sulfate and 2M zinc salt electrolyte to construct aqueous zinc-manganese batteries. Specifically, the positive electrode materials provided in Examples 1 to 7 and Comparative Example 1 were used as positive electrodes, zinc foil was used as negative electrodes, and the electrolytes were 2M ZnSO4 and 0.2M MnSO4. The batteries were subjected to charge and discharge tests and charge and discharge long cycle tests. The results are as follows: Figures 8 to 13 shown.
[0108] The positive electrode materials provided in Examples 1 to 7 were subjected to long-cycle charge and discharge tests. Since the results are similar, only the test results of Example 4 are used as an example for illustration below. Figure 8 The positive electrode material provided in Example 4 and Comparative Example 1 is used as the positive electrode of the zinc ion battery at 500 mA g -1 The long cycle of charge and discharge under current density. Figure 8 It can be seen that at a current density of 0.5A g -1 Under the condition of , after 150 charge-discharge cycles, the capacity retention rate of the positive electrode material of Example 4 (P-MnO2 in the figure) is almost perfectly maintained at 100%, and its specific capacity is still as high as 341 mAh g -1 , showing excellent cycle stability. In comparison, the performance of the positive electrode material in comparative example 1 (MnO2 in the figure) is much worse, with a capacity retention rate of only 67% during the same period, and a corresponding specific capacity of only 98 mAh g -1 .
[0109] The positive electrode materials provided in Examples 1 to 5 were subjected to charge and discharge tests. Since the results are similar, only the test results of Example 4 are used as an example for illustration below. Fig. 9 , 10 The rate performance and corresponding charge-discharge curves of the positive electrode material provided in Example 4 at different current densities. The current densities used for constant current charge and discharge are 0.2, 0.5, 1, 1.5, 2, 3, and 5 A g -1 The positive electrode material of Example 4 (P-MnO2 in the figure) was 0.2, 0.5, 1.0, 1.5, 2.0, 3.0 and 5.0 Ag. -1 The average discharge capacities at 4000 mAh g were 510.2, 406.3, 329.8, 283.3, 250.6, 209.7 and 164.1 mAh g -1 The overall performance shows a high capacity output and a relatively stable change with the current density. Compared with the unmodified positive electrode material of the same material in Example 1 (MnO2 in the figure), its rate performance has a significant advantage. -1 The first 20 cycles from the initial 380mAh g -1 Increased to 520mAh g-1 , a significant capacity increase can be observed, which indicates that with the formation of “proton self-confinement domains” within the PANI layer, the MnO2 / Mn 2+ The reaction is gradually stimulated. Considering the interfacial Mn-N bonds and the reversible MnO2 deposition reaction, the excellent battery performance of P-MnO2 can be attributed to the MnO2 being encapsulated in the proton-rich polyaniline protective layer.
[0110] Fig.11 The positive electrode material of Example 1-5 is used as a zinc ion positive electrode material in 200mAg -1 The charge and discharge cycle diagram under the current density of Fig.10 It can be seen that in the composite material system, when the proportion of polyaniline is low, its impact on battery performance is basically maintained at 225mAh g -1 On the contrary, once the proportion of polyaniline is too high, it will cause negative effects, resulting in a sharp decrease in the number of battery cycles and seriously reducing the cycle life of the battery. Therefore, the difference in the ratio of polyaniline to manganese dioxide will have a significant impact on the experimental results. When the ratio of the two is within an appropriate range, the coating effect of polyaniline on manganese dioxide is better, which can not only effectively improve the structural stability of manganese dioxide, but also significantly enhance the overall conductivity of the positive electrode material, promote the efficient deintercalation of hydrogen ions, and further improve the specific capacity and cycle stability of aqueous zinc-manganese batteries.
[0111] Fig.12 The positive electrode material provided in Examples 6, 7 and Comparative Example 1 is used as a zinc ion positive electrode at 1000 mAg -1 The charge and discharge long cycle diagram at the current density of . Fig.11 It can be seen that even if the manganese dioxide in the positive electrode material is replaced by manganese trioxide or manganese tetraoxide, a significant improvement can still be achieved in capacity and stability. This fully demonstrates that the effective action range of polyaniline is not limited to manganese dioxide, and it has a very significant promoting effect on various manganese oxides.
[0112] Fig.13 The positive electrode material provided in Example 4 and Comparative Example 1 is used as a zinc ion positive electrode at 5000 mAg -1 The charge and discharge long cycle diagram at the current density of . Fig.12 It can be seen that at 5000mAg -1 Under high current density, the positive electrode material of Example 4 still exhibits amazing long cycle stability. After up to 10,000 charge and discharge cycle tests, its capacity retention rate is still as high as 94%, the battery can still maintain excellent stability, and its specific capacity can also be maintained at a good level, which fully demonstrates the excellent performance of the positive electrode material under high current conditions.
Claims
1. An interface optimized material, characterized in that: The interface optimized material comprises: polyaniline and manganese oxide; The polyaniline is coated on the surface of the manganese oxide to form a polyaniline layer, and a Mn-N bond is formed between the polyaniline and the manganese oxide.
2. The interface optimized material according to claim 1, characterized in that: The mass ratio of the polyaniline to the manganese oxide is (0.05-0.30):
1.
3. The interface optimized material according to claim 1, characterized in that: The thickness of the polyaniline layer is 5-10 nm.
4. The interface optimized material according to claim 1, characterized in that: The manganese oxide is one or more of manganese dioxide, dimanganese trioxide or trimanganese tetraoxide.
5. A method for preparing an interface optimized material, characterized in that: The method comprises the following steps: dispersing manganese oxide and polyaniline in an organic solvent and stirring to obtain a mixed solution; After adding the conductive powder to the above mixed solution, transfer it to a hydrothermal kettle and heat it at 60°C to 80°C for 4 to 6 hours; After the reaction is completed, part of the conductive powder is removed by centrifugation, and then dried to obtain the interface optimized material.
6. The method for preparing the interface optimized material according to claim 5, characterized in that: The mass ratio of the polyaniline to the manganese oxide is (0.05-0.30):1; The mass ratio of the conductive powder to the manganese oxide is (0.02-0.10):
1.
7. Use of the interface optimized material according to claims 1 to 4 as positive electrode material for zinc ion batteries.
8. A method for preparing a positive electrode material, characterized in that: The preparation method comprises the following steps: adding the interface optimization material according to any one of claims 1 to 4: conductive agent: binder in a mass ratio of (6 to 8): (3 to 1): 1 to a solvent, grinding and mixing, coating on a current collector, and drying to obtain a positive electrode material.
9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises: a positive electrode material layer; the positive electrode material layer comprises the interface optimized material according to any one of claims 1 to 4 or the positive electrode material prepared by the preparation method according to any one of claims 5 to 10.
10. A zinc ion battery, characterized in that: The battery comprises the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Novel battery
CN102856557A
Preparation method of MnO2 / rGO / PANI aerogel and application of MnO2 / rGO / PANI aerogel in aqueous zinc ion battery
CN110808359A
Manganese-based oxide electrode with improved electrode density and manufacturing method thereof and aqueous zinc ion battery including the same
KR102703437B1